2004
DOI: 10.1007/s00535-004-1423-9
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of angiogenic factors in the VEGF-Ets-1 cascades in inflammatory bowel disease

Abstract: Angiogenic factors in the VEGF-Ets-1 cascades were upregulated in UC, but they were relatively downregulated in CD. These alterations might be involved in the pathogenesis of both diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
15
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 41 publications
5
15
2
1
Order By: Relevance
“…In previous studies, an increased expression of VEGF protein and VEGF mRNA in UC patients had already been observed in comparison with those found in healthy controls [25,[34][35][36][37][38]. Our results were consistent with those found in previous studies using active UC patient blood samples [25,34,35].…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…In previous studies, an increased expression of VEGF protein and VEGF mRNA in UC patients had already been observed in comparison with those found in healthy controls [25,[34][35][36][37][38]. Our results were consistent with those found in previous studies using active UC patient blood samples [25,34,35].…”
Section: Discussionsupporting
confidence: 95%
“…Regarding the VEGFR1 tissue expression in these patients, there were diverse results in previous studies. Similarly, other authors also found an increased expression of both VEGFR1 protein and mRNA in UC inflamed mucosa [37].…”
Section: Discussionmentioning
confidence: 93%
“…The increase in VEGF expression is mostly evident in the crypt region of the pouch mucosa, whereas in the ileal nonpouch mucosa obtained from the same patients and in the control ileal mucosa from patients with IBS, the immunostaining for VEGF is almost totally confined to the superficial epithelium. An increase in VEGF expression has previously been reported in the mucosa of patients with inflammatory bowel disease 23,24 and particularly in patients with ulcerative colitis. 25 To our knowledge this is the first report that shows upregulation of VEGF expression in IPAA.…”
Section: Discussionmentioning
confidence: 94%
“…49 Studies have indicated reduced expression of Ets1 in PBMCs of patients with systemic lupus erythematosus and patients with inflammatory bowel disease. 50,51 Ets1 has also been reported to regulate the suppressive activity of MDSCs in tolerance induction to CD8 1 T cells. 52 Glucocorticoids modulate cell fate by altering gene expression via the glucocorticoid receptor (GR).…”
Section: Discussionmentioning
confidence: 99%